The relationship of transformational leadership of the head of the madrasa and boarding school with the tahfizd ability of the Qur'an students at MA Shaykh Zainuddin NW Anjani - sibawaih, sibawaih; Rasidi, Ahyar; Citriadin, Yudin; Wahyudiati, Dwi (Jurnal Ilmiah Mandala Education (JIME), 2024)
The transformational leadership of the head of the Madrasah and boarding school is a unity that supports in determining the success of students to become tahfizd al-Qur'an. Madrasah that applies its learning with  the boarding school system  which is its flagship program is tahfizd al-qur'an. This study used a quantitative approach with a type of survey research.  The total population in this study amounted to 100 people while the sample amounted to 49 people. To obtain data in this study, questionnaires were used, data analysis used SPSS 16 and multiple correlation coefficients. The results showed that the double correlation coefficient analysis obtained a value of 0.788. After being tested significantly with an F test at a significant level of 5%, there was a significant relationship between transformational  leadership and boarding school with students' Qur'anic tahfizd ability and the magnitude of transformational leadership and boarding school  contribution with students' Qur'anic tahfiz proficiency at MA Shaykh Zainuddin NW Anjani of 0.605.